Psychological Characteristics Of The Development Of Generosity In Children - Jorakulova Dildora Ziyodullaevna (Genius Publishing Group, 2022)
Greed is far from being the most attractive human trait. Excessively greedy people are perceived by society as a rule negatively. Yes, and for them their greed can cause a lot of problems.
Keywords: Generosity; greed; jealousy; envy